Oncocytic Carcinoma of the Cranio-Orbital Area: A Case Report - Yang, Peng; Jiang, Libin; Liu, Honggang; Zhang, Jialiang; Kang, Jun (Frontiers in Surgery, 2022)
Oncocytic carcinoma is a malignant tumor characterized by a proliferation of epithelial cells with abundant eosinophilic granular cytoplasm. In this article, we report on the first case of a 61-year-old male patient presenting with oncocytic carcinoma involving the cranio-orbital area. An oncocytic carcinoma in the patient, who reported a sudden decrease in vision in his right eye, was removed through a frontal orbital approach craniotomy. The patient's postoperative development was rapid, and he was admitted to the neurosurgery department for a combined operation after ophthalmological screening. Pathological analysis revealed the tumour cells were large, round or polygonal, and the cytoplasm was finely granular and appeared to be more pleomorphic than the eosinophilic adenoma. Oncocytic carcinoma in the cranio-orbital area is extremely rare. The most effective treatment is early resection to be performed jointly by ophthalmology and neurosurgery, and long-term follow-up and adjuvant chemoradiotherapy are beneficial.